Imatinib use in the management of a patient with Doege–Potter syndrome - Paz-Ibarra, Jose (2023)
“Doege–Potter syndrome (DPS) is a paraneoplastic syndrome characterized by nonislet cell tumor hypoglycemia due to a solitary fibrous tumor, which produces insulin-like growth factor II. In this report, we present the case of a 67-year-old male with recurrent and refractory hypoglycemia due to DPS successfully treated with imatinib. He initially presented with neuroglycopenic symptoms and dyspnea secondary to a giant tumor in the left hemithorax, which was totally resected. During follow-up, 7 years later, he presented with thoracoabdominal tumor recurrence associated with severe hypoglycemia and underwent subtotal tumor resection, with a subsequent improvement of symptoms. The following year, he had a recurrence of his intra-abdominal tumor, which was unresectable, associated with severe hypoglycemia refractory to dextrose infusion and corticosteroids, thus receiving imatinib with a favorable response. The clinical presentation, diagnostic approach, progression of the disease, and response to treatment with imatinib in the management of a patient with large, recurrent, and unresectable mesenchymal tumors with insulin-like growth factor-2 secretion causing hypoglycemia highlight the importance of this case report“